Tokenomics: When Tokens Beat Equity - Malinova, Katya; Park, Andreas (Management Science, 2023)
In a token offering, investors fund a venture in exchange for tokens that grant rights to future economic output. To many financial industry insiders, tokens have no intrinsic merit and exist only as a way to evade regulations. We demonstrate that generic revenue-based token contracts are indeed economically inferior to equity and lead to over- or underproduction. However, an optimally designed token contract, which is a combination of an output presale and an incremental revenue-sharing agreement, yields the same payoffs as equity and debt. Moreover, with entrepreneurial moral hazard, tokens can finance a strictly larger set of ventures than equity. This paper was accepted by Will Cong, Special Section of Management Science: Blockchains and Crypto Economics. Funding: This work was supported by the Social Sciences and Humanities Research Council of Canada and Canadian Securities Institute Research Foundation [Grants 20013075 and 435-2017-064]. Financial support from the Global Risk Institute and the Mackenzie Investment Chair in Evidence-Based Decision Making is also acknowledged.